Nature and extent of forest resource extraction from Modhupur Sal forest by the community - Nayeem, FMH; Hoque, MN; Ali, M; Islam, MM; Haque, S (Progressive Agriculture, 2017)
The study was undertaken to document the nature and extent of forest resource extraction from the Modhupur Sal forest by the community people. It was conducted at Rosulpur village in Muktagachha Upazila which is adjacent to Modhupur Upazila of Tangail district. A total of 60 households were selected for data collection using purposive sampling technique. The collected data through field survey method were analyzed using descriptive statistics. The majority of the forest users was aged between 25 to 34 years and had a literacy status of below secondary school certificate level. Around 30% of the forest users depend on agriculture but forest resource extraction was the subsidiary occupation for most of the households that was done by mostly female members of the respondents family. Forty percent of the forest users income varies from Tk. 10000 to Tk. 15000 per month. Besides these, majority of them had 0.51 to 1.0 acre of cultivable lands. Though different resources are extracted from Modhupur Sal forest such as timber, fuel wood, medicinal plants, etc, but timber is collected by 100% of the respondents. Number of livestock, level of landholding and labor time spent for forest resources collection were the influencing factors for households forest resources collection. The majority of the forest users suggested that government need to invest in awareness building program and enforce rules and regulations so that community people can contribute and participate to conserve the forest. Progressive Agriculture 28 (2): 148-155, 2017